STRATEGI DINAS PERTANIAN DAN PERKEBUNAN KABUPATEN MINAHASA DALAM MENINGKATKAN PRODUKSI PERTANIAN - Regita Agatha Valencia Rumagit; Rully Mambo; JOYCE RARES (Sam Ratulangi University, 2023)
This study aims to determine the Strategy of the Agriculture and Plantation Office in Minahasa district in Increasing Agricultural Production. This study used qualitative descriptive method using SWOT data analysis. SWOT analysis is used with the Internal Summary Matrix (IFAS) and the External Factory Analysis Summary (EFAS) to show the current position of the organization. From the results of the data analysis, the Minahasa Regency Agriculture and Plantation Office is currently in a position between the Opportunities and Weaknesses sumbe, namely Quadrant III (W-O Strategy), where the Agriculture and Plantation Office in Minahasa Regency gets external opportunities, but on the other hand it experiences several internal obstacles/problems. So in such conditions the Department of Agriculture and Plantation needs to carry out a Trun Around strategy, namely fixing or minimizing internal organizational problems so that it can seize opportunities from outside well. Based on the results of the SWOT analysis, there are 13 strategic issues which are then continued with testing the strategic level of issues with the Litmus Test and through the Litmus test there are 8 issues that fall into the strategic category, namely issues about further developing agricultural facilities with adequate infrastructure and infrastructure support to further improve again the efficiency, productivity and sustainability of the agricultural sector, issues regarding providing agricultural education to farmers regarding the correct use of agricultural facilities, regarding how to operate, maintain and carry out preventive maintenance to minimize the risk of damage, issues regarding taking advantage of market opportunities that are still open so that further optimizing the role of farmer groups by cultivating idle land so that it can be utilized, issues about optimizing the use of agricultural infrastructure and facilities as well as further developing science and technology in existing agriculture such as tractors and irrigation channels, even though the amount of infrastructure is not much, issues about developing farmers' knowledge and skills to increase access to capital through the support of natural resources and wide open market opportunities, issues about focusing on increasing agricultural products and increasing farmers' knowledge, abilities and capital to strengthen their bargaining position in agriculture, issues about optimizing agricultural land use by support from existing natural resources, as well as having a clear comprehensive plan, to reduce land conversion due to many public needs, the issue of establishing an affordable and reliable agricultural insurance program to protect farmers from the risk of extreme weather changes and normal weather changes.